Synthetic or Real? The Equilibrium Effects of Credit Default Swaps on Bond Markets - Oehmke, Martin; Zawadowski, Adam (Review of Financial Studies, 2015)
We provide a model of nonredundant credit default swaps (CDSs), building on the observation that CDSs have lower trading costs than bonds. CDS introduction involves a trade-off: it crowds out existing demand for the bond, but improves the bond allocation by allowing long-term investors to become levered basis traders and absorb more of the bond supply. We characterize conditions under which CDS introduction raises bond prices. The model predicts a negative CDS-bond basis, as well as turnover and price impact patterns that are consistent with empirical evidence. We also show that a ban on naked CDSs can raise borrowing costs.